Simultaneous determination of furan and 2-alkylfurans in heat-processed foods by automated static headspace gas chromatography-mass spectrometry. (October 2016) - Shen, Mingyue; Liu, Qian; Jia, Hanbing; Jiang, Yujie; Nie, Shaoping; Xie, Jianhua; Li, Chang; Xie, Mingyong
Abstract: In this study, the levels of furan and 2-alkylfurans (2-methylfuran, 2-ethylfuran, 2, 5-dimethylfuran, 2-propylfuran, 2-butylfuran, 2-pentylfuran) were determined in a variety of foodstuffs by static headspace gas chromatography and mass spectrometry. The headspace operating conditions and the effects of food matrix on the responses of analytes were investigated. Besides, the co-elution of 2-ethylfuran/2, 5-dimethylfuran was processed using the automated deconvolution software for the correct identification and quantification of 2-ethylfuran and 2, 5-dimethylfuran in food samples. The external matrix matched standard calibration method was chosen to correct the matrix effects for the analysis of furan and 2-alkylfurans in a total of 126 food samples. Results showed that furan and 2-alkylfurans were detected in 70.6% of food samples with total concentrations ranging from 0.5 to 789.4 ng g −1 . Highlights: The levels of furan and 2-alkylfurans were determined in a variety of foodstuffs. The coelution of analytes was processed using the automated deconvolution software. Matrix-matched calibration curves were used to compensate the matrix effects.